PERAN THE INSTITUTE FOR PEACE AND DEMOCRACY (IPD) DALAM DEMOKRATISASI DI MYANMAR - Wilson Rojeki Sidauruk; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research explains and proves the role of The Institute for Peace and Democracy (IPD) in growing and developing democractization in Myanmar from military Junta. Myanmar has been led fifty years by military Junta.Perspective that used in this research is institutionalism perspective. This research also uses the role theory. The theory asserts that the role of political behavior is the behavior of the running political role. This theory assumes that the majority of political behavior is a result of the demands or expectations of the role held by political actors. An institution has the role in giving impact according of their mission. This research also used literatures research methodology by colleting data from many literatures such as books, journals, and websites.Institute for Peace and Democracy has mission in seeking and finding ways of democracy suitable for Myanmr with cultures and norms of life. IPD cooperate with Myanmar's government and civil society in designing and implementing capacity development programs in the country. IPD has been making some programs that related with democracy and also giving positive impact for Myanmar especially. This research proves that IPD is not only as common institue but also have strong commitment in helping Myanmar to be optimist and go up to get freedom and to be democratic country.Key words : Democratization, IPD, Myanmar, military junta.